PERBANDINGAN ANTARA MARINE ACOUSTIC REMOTE SENSING DAN SWEPT AREA TRAWL DALAM PENDUGAAN DENSITAS IKAN DEMERSAL DI PERAIRAN TARAKAN - Simbolon, Domu; Priatna, Asep; Hestirianoto, Totok; Purbayanto, Ari (Jurnal Penginderaan Jauh dan Pengolahan Data Citra Digital, 2015)
The use of hydroacoustic surveys simultaneously with trawl swept area is expected to complement and increase the accuracy each other in estimation of the fish stock resources, especially demersal fish. Therefore, advantages and disadvantages of each method will be disclosed. The purpose of this study was to compare the density of demersal fish from detection of hydroacoustic surveys toward catches of bottom trawl, and to determine the factors that influence differences in fish density estimated of swept area and acoustic method. The study was conducted on May, August and November 2012 around Tarakan waters, North Borneo, using echo sounder Simrad EY60-120 kHz and bottom trawl simultaneously to measure density of demersal fish. Demersal fish density estimation of the two methods showed a highly significant difference. Difference in the estimation of fish density was affected by catchability, dead zone area of trawling, and fish behavior.